Estudo clínico e níveis de ansiedade em uma série de casos de líquen plano oral - Barbosa, Natália Guimarães (2012)
Oral Lichen Planus (OLP) is a relatively common, cronic inflammatory disease. Its etiopathogenesis is no completely understood and several factors have proposed in attempt to explain the appearance, variety of clinical manifestations and periods of exacerbation and remission of the symptons of the lesions. The objective of the present study was to assess the presence of local factors, systemic diseases and levels of anxiety in patients with OLP, investigating their association with the clinical characteristics of the lesions. The sample consisted of 37 patients with histopathologically confirmed OLP that were submitted to a clinical exam to evaluate the presence of smoking habits, consumption of alcoholic beverages, diabetes mellitus, hypertension and hepatitis C virus (HCV) infection. The existence of skin lesions, as well as the time course, clinical form, symptomatology, number and location of the oral lesions were also registered. The trait anxiety was measured by Spielberger s Stai-Trait Anxiety Inventory (STAI), and to associate the variables we used the chi-square or Fisher s exact test. It was observed that females were the most affected (75%) and the mean age of the patients was 53,3 years. Most cases were non-smoker (97,3%) and none was drinker. Diabetes mellitus and hypertension were present in 10,8% e 16,2% of the sample, respectively and only one patient was HCV-seropositive (2,7%). Moderate levels of anxiety were seen in most cases (78,4%) and 21,6% had elevated levels. The oral lesions persisted in 95% of the cases for a period of 6 months to 13 years. The erosive form was the most prevalent (57,1%) and symptons were reported by 45,7% of the patients. Multiple lesions were frequent (60%), affecting mainly the buccal mucosa, followed by gums e tongue. There was no significant association of the presence of diabetes mellitus, hypertension and levels of anxiety with the clinical form or symptomatology of the oral lesions (p>0,005), despite a trend in patients with hypertension to have erosive lesions. It was concluded that, in the sample studied, moderate levels of anxiety were commonly observed, and the HCV infection apparently is not related to the onset of the OLP. In this study, the presence of diabetes mellitus, hypertension and levels of anxiety seem not to be associated with the clinical characteristics of the lesions of OLP